Unmasking the seronegative autoimmune hepatitis: The hunt for novel autoimmune markers - Tawheed, Ahmed; Ozercan, Mubin; Bahcecioglu, Ibrahim Halil; Yalniz, Mehmet; El-Kassas, Mohamed (Research Trends (P) LTD., 2023)
Autoimmune hepatitis (AIH) is the most common autoimmune disease of the liver. There has been an increase in the incidence of AIH over the last few years. There are different scoring systems to diagnose AIH, and they all depend on the presence of autoantibodies like anti-nuclear antibodies (ANA), anti-smooth muscle antibodies (ASMA), anti-liver kidney microsome antibodies (LKM), and anti-soluble liver antigen (SLA). Those antibodies could be absent in nearly 10% of patients with AIH, making the diagnosis using the current scores difficult. Also, some studies reported a more severe disease course in those with seronegative AIH. The absence of autoantibodies has been explained by several theories, including the presence of defects in B cell maturation and pseudo-seronegativity. However, the pathogenesis of seronegative AIH remains very similar to that of seropositive AIH. Currently, the diagnosis of seronegative AIH requires evaluation of personal and family medical history, clinical symptoms, and specific laboratory tests, including hypogammaglobulinemia, as well as a liver biopsy. Recently, multiple autoimmune markers have been proposed to facilitate the diagnosis of seronegative AIH, such as anti-actin antibodies, anti-asialoglycoprotein, polyreactive IgG (pIgG), HLA DR4, HLA B8, and HLA CW7. Both AIH and seronegative AIH have the same treatment recommendations, and the results of treatment responses are comparable in both groups. Furthermore, it was reported that in some patients with seronegative AIH, immunosuppressive treatment could turn the antibody status into positivity. This review article provides a comprehensive overview of seronegative AIH, including its clinical features, potential autoimmune indicators for seronegative AIH, and a suggested diagnostic algorithm for those patients. © 2023, Research Trends (P) LTD.. All rights reserved.
Keywords: ANA; ASMA; autoimmune hepatitis; liver; seronegative